Nuclear Localization and Functional Characteristics of Voltage-gated Potassium Channel Kv1.3 - Jang, Soo Hwa (J Biol Chem, 2015)
It is widely known that ion channels are expressed in the plasma membrane. However, a few studies have suggested that several ion channels including voltage-gated K(+) (Kv) channels also exist in intracellular organelles where they are involved in the biochemical events associated with cell signaling. In the present study, Western blot analysis using fractionated protein clearly indicates that Kv1.3 channels are expressed in the nuclei of MCF7, A549, and SNU-484 cancer cells and human brain tissues. In addition, Kv1.3 is located in the plasma membrane and the nucleus of Jurkat T cells. Nuclear membrane hyperpolarization after treatment with margatoxin (MgTX), a specific blocker of Kv1.3 channels, provides evidence for functional channels at the nuclear membrane of A549 cells. MgTX-induced hyperpolarization is abolished in the nuclei of Kv1.3 silenced cells, and the effects of MgTX are dependent on the magnitude of the K(+) gradient across the nuclear membrane. Selective Kv1.3 blockers induce the phosphorylation of cAMP response element-binding protein (CREB) and c-Fos activation. Moreover, Kv1.3 is shown to form a complex with the upstream binding factor 1 in the nucleus. Chromatin immunoprecipitation assay reveals that Sp1 transcription factor is directly bound to the promoter region of the Kv1.3 gene, and the Sp1 regulates Kv1.3 expression in the nucleus of A549 cells. These results demonstrate that Kv1.3 channels are primarily localized in the nucleus of several types of cancer cells and human brain tissues where they are capable of regulating nuclear membrane potential and activation of transcription factors, such as phosphorylated CREB and c-Fos.